Adsorption Characteristics of Coconut Husk Biochar for Organics in Water - Vo Cong Minh; Nguyen Nhat Huy; Thuy Nguyen Thi; Lien Thi Le Nguyen (Indonesian Journal of Chemistry)
Biochar was produced from coconut husk by simple pyrolysis at 600 °C, aiming for low-cost production. The biochar was characterized and studied for adsorption of four types of antibiotics and organic contaminants, which were levofloxacin (LEV), doxycycline (DOX), tartrazine (Tar), and rhodamine B (RhB), in water. The EDX and FTIR analysis shows homogeneous active centers of the biochar. The high surface area, i.e., 664.66 m2/g, and total pore volume of 0.8159 cm3/g were determined by BET analysis, and the pore structure observed in SEM shows the appropriation of the material for adsorption of organic contaminants in the water. Adsorption conditions were studied and the results revealed that the adsorption mechanism varies among different adsorbate’s molecular structures. The result shows that cationic dye (RhB) is better absorbed by the coconut biochar than anionic dye (Tar) and the covalent antibiotic (DOX, LEV). The maximal adsorption capacities under optimal pH conditions were 172.41 mgRhB/g, 48.31 mgDOX/g, 42.37 mgLEV/g, and 21.37 mgTar/g. The best experimental fit for the adsorption data was Langmuir isotherm. The thermodynamic studies implied that the adsorption mechanism was physical adsorption (e.g., LEV, DOX, Tar), while RhB adsorption is more likely to be chemisorbed.